EVERYDAY WATERCOLOR flowers : A MODERN GUIDE TO PAINTING BLOOMS, LEAVES, AND STEMS STEP BY STEP - Rainey, Jenna, 1989- (Berkeley, California : Watson-Guptill, 2019)
Author of Everyday Watercolor and Instagram darling Jenna Rainey presents a beautiful step-by-step guide to painting botanicals from lilies to daffodils in a wide variety of styles. Artist Jenna Rainey shares easy-to-follow ways to paint a wide range of botanicals, all in her fresh, modern style that appeals to the next generation of watercolor artists and creatives, from beginners to hobbyists. With gorgeously illustrated instructions for both loose and realistic watercolor depictions of more than 25 flowers, leaves, and plants, organized by form and shape, Everyday Watercolor Flowers is every nature-lover's answer to capturing that beauty on paper.
Includes bibliographical references and index
Keywords: Flowers in art; Watercolor -- Technique; Flowers in art